ANALISIS INDUSTRI RUMAH TANGGA GULA SEMUT UNTUK EKSPOR DI KABUPATEN KULON PROGO DAN PURWOREJO - Fransisca Nugraheni Putri Prihtanto; Irham Irham; Any Suryantini (Department of Agricultural Socio-Economics Faculty of Agriculture Universitas Gadjah Mada, 2015)
This study aims to: 1) measure the feasibility of granular brown sugar household industry for export in Kulon Progo and Purworejo districts, 2) determine the value added of the granular brown sugar, 3) determine differences in income, profits, and value added of both industries, 4) determine the factors that affect value added of granular brown sugar, ·5) analyze the sensitivity of the breakeven point with input, output, and exchange rate. The results indicatesthat the granular brown sugar household industries are feasible to develop and provide benefits for business owners. However the household industry of granular brown sugar in Kulon Progo made of brown sugar based on 1C/C ratioshow that the industry is not feasible to develop. The study also shows that the value added of the granular brown sugar made of brown sugar and that made of coconut sap in Kulon Progo are Rp 1.427 and Rp 793. While, the valueadded of granular brown sugar in Purworejo is Rp 644. The results of one way ANOVA show that there is no income or profits difference among respondents groups of the granular brown sugar household industry, but there is a differenceof value added among respondents groups of the granular brown sugar household industry. Factors that significantly influence the value added are: the production capacity, the output price, and the amount of labor. Household industry of granular brown sugar in the third group of business are very sensitive to input and output price reductions and decline in the exchange rate up to 30% still give the profit to the exporter.